Platelet Count and Platelet Stickiness in Rats - Grüner, O. P. N; Endresen, G. K. M (Thrombosis and Haemostasis, 1971)
In rat, a transected tail vessel proved an adequate source of blood for platelet enumeration. When suspensions of rat blood in ammonium oxalate were rotated for 1 h a significant loss of platelets was observed. This platelet reduction rate (PRR), calculated as per cent of the pre-rotation count, showed individual constancy and inter-individual variance.